Drivers of CO2-carbonate system variability in the coastal ocean south of Honolulu, Hawai’i - Knor, Lucie A. C. M.; Meléndez, Melissa; Sabine, Christopher L.; Sutton, Adrienne J. (Frontiers in Marine Science, 2024)
This study examines carbonate chemistry variability from 2008 to 2021 in subtropical coastal waters adjacent to Honolulu, Hawai’i. We use surface seawater carbon dioxide partial pressure (pCO2sw) measurements obtained every three hours from two buoys located along the south shore of O’ahu near anthropogenically impacted fringing reefs. The Ala Wai buoy was located 200 m offshore of a canal draining most of Honolulu, while the Kilo Nalu buoy was 1.3 miles (2 km) to the northwest, at a similar distance from shore with fewer terrestrial inputs. We compare pCO2sw variability from diurnal to interannual time scales. A trend analysis reveals a statistically significant increase in pCO2sw of +1.84 ± 0.27 µatm per year over the 11-year period. This rate is slightly lower than the average atmospheric growth rate observed during the same timeframe. In contrast to a nearby open-ocean site, the coastal sites experience amplified shorter-term variability, while seasonal to inter-annual variability is comparable to the open ocean. Ala Wai exhibits greater ranges than Kilo Nalu in all carbonate system variables due to its proximity to the Ala Wai Canal outflow. We examine the drivers that may explain both the similarities and contrasts in carbon dynamics observed between the two locations. Drivers of aragonite saturation state (ΩAr), an important variable for quantifying ocean acidification, are isolated from the in-situ time-series. Interannual salinity variations both due to freshwater pulses and large-scale regional salinity changes have a larger impact on ΩAr than temperature changes, which mostly have an effect seasonally. A large biological contribution to ΩAr is suspected, and further investigated using TA/DIC ratios normalized to median salinity and their slopes. Observed ratios at the south shore sites are evaluated relative to expected ratios derived from an open-ocean reference. Results suggest that dissolution and respiration are the primary biogeochemical processes occurring at these coastal sites. This highlights the significance of carbonate dissolution in anthropogenically impacted coastal waters, which is likely buffering acidification due to anthropogenic CO2 and freshwater inputs at these sites.